1977
DOI: 10.1111/j.1540-6261.1977.tb03279.x
|View full text |Cite
|
Sign up to set email alerts
|

Value and Yield Risk on Outstanding Insured Residential Mortgages

Abstract: THIS PAPER PRESENTS an analytically rigorous method for estimating the value of an outstanding residential mortgage and for determining the error between this correct method of determining value and conventional or "rule-of-thumb" methods. It also develops a procedure for determining the likely error in the correctly estimated value associated with potential divergence between estimated and realized cash flows. The paper builds on a methodology for calculating expected mortgage yield which was described in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…For a given contract rate the effective rate to the mortgagee increases as the discount increases. The effective rate increases by a much larger percent for shorter holding periods; see Curley and Guttentag (1977).…”
Section: Motivation Of the Studymentioning
confidence: 99%
“…For a given contract rate the effective rate to the mortgagee increases as the discount increases. The effective rate increases by a much larger percent for shorter holding periods; see Curley and Guttentag (1977).…”
Section: Motivation Of the Studymentioning
confidence: 99%
“…This paper prices the interest rate differential on default-free hypothetical early equity mortgages using yield curve data from 1970 to 1984. Studies by Curley and Guttentag (1977), Kaufman and Morgan (1980), and others have shown that conventionally computed yields on mortgages must be adjusted to make them comparable to other securities. Other studies have applied the option pricing framework to conventional mortgages [see Dunn and McConnell (1981) and Buser and Hendershott (1984)].…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…Only insurers, predominantly the FHA, were concerned about the timing of payments and eventual disposition of mortgages. Thus, FHA termination data have been the factual basis for several analyses, such as Curley and Guttentag (1974) and Waldman (1981). Curley and Guttentag (1974) use ordinary least squares (OLS) to regress the logarithm of the annual termination rate (defined as the number of loans that either prepay or default during the year divided by the number outstanding at the beginning of the year) against three explanatory factors: the annual average interest-rate differential, the discount (points) that prevailed during the current year, and the logarithm of the ratio of the policy year to the year of maturity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This can be done most easily through the use of a "fixed-effects" or "covariance" model, in which dummy variables are used to allow each pool and time period to have a different intercept, but the effect of DIF and the other explanatory variables is assumed to be the same across pools and stationary 2Secause the divisor is the beginning-of-period balances, this problem is mitigated to some extent, particularly for mortgages that were outstanding for two or more years. Greater precision would result, however, if a "policy year" variable, such as that used by Curley and Guttentag (1974) and by Peters, Pinkus, and Askin (1984), could be constructed. over time.…”
Section: The Model and The Datamentioning
confidence: 99%